ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN E-LKPD BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI SISTEM PERIODIK UNSUR BERBANTUAN LIVEWORKSHEET - Nurhayati, Nurhayati; Aini, Syamsi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Chemistry learning on the crucial topic of the periodic table of elements (SPU) at SMTI Padang Vocational High School (SMTI) is identified as still facing challenges, despite utilizing learning resources such as textbooks and PowerPoint. The background to this problem is the low understanding of SPU concepts (61.8% of students find them difficult) and the existing teaching materials are considered less interactive (90.9% of students have difficulty understanding them), thus not optimally fostering critical thinking skills. This study focuses on analyzing the needs for developing innovative learning media in the form of Electronic Student Worksheets (e-LKPD) based on Problem-Based Learning (PBL) with the assistance of the Liveworksheet platform. A crucial stage of this research is the Define stage of the 4D development model, which was conducted through in-depth interviews with three teachers and the distribution of needs questionnaires to 55 Phase E students. Key findings revealed a gap between actual conditions and learning needs; teachers require interactive PBL media relevant to industrial contexts, while students (50% of whom have a visual learning style) strongly desire digital media. Key findings supporting this solution include infrastructure readiness (100% of students brought devices; 92.7% had internet access) and high student interest (83.6%). Therefore, it is concluded that the development of PBL-based e-LKPD with the assistance of Liveworksheet is a highly relevant and necessary solution for creating more interactive, flexible, and meaningful SPU learning. ABSTRAKPembelajaran kimia pada materi krusial sistem periodik unsur (SPU) di SMK SMTI Padang diidentifikasi masih menghadapi kendala, meskipun telah memanfaatkan sumber belajar seperti buku teks dan PowerPoint. Latar belakang masalah ini adalah rendahnya pemahaman konsep SPU (61,8% siswa merasa sulit) dan bahan ajar yang ada dinilai kurang interaktif (90,9% siswa kesulitan memahaminya), sehingga belum optimal menumbuhkan keterampilan berpikir kritis. Penelitian ini berfokus pada analisis kebutuhan pengembangan media pembelajaran inovatif berupa Lembar Kerja Peserta Didik Elektronik (e-LKPD) berbasis Problem Based Learning (PBL) dengan bantuan platform Liveworksheet. Tahapan penting penelitian ini adalah tahap Define dari model pengembangan 4D, yang dilaksanakan melalui wawancara mendalam dengan tiga guru dan penyebaran angket kebutuhan kepada 55 siswa Fase E. Temuan utama mengungkap adanya kesenjangan antara kondisi aktual dan kebutuhan pembelajaran; guru memerlukan media PBL yang interaktif dan relevan dengan konteks industri, sementara siswa (50% bergaya belajar visual) sangat menginginkan media digital. Temuan kunci yang mendukung solusi ini adalah kesiapan infrastruktur (100% siswa membawa gawai; 92,7% akses internet) dan minat siswa yang tinggi (83,6%). Dengan demikian, disimpulkan bahwa pengembangan e-LKPD berbasis PBL berbantuan Liveworksheet merupakan solusi yang sangat relevan dan dibutuhkan untuk menciptakan pembelajaran SPU yang lebih interaktif, fleksibel, dan bermakna.